Biodata Mobilisation of the Entomological Collections of the Schmalhausen Institute of Zoology of the National Academy of Sciences of Ukraine - Andriy Babytskiy; Maryna Kaliuzhna; Oleksandr Varga; Vitalii Kavurka; Alexey Prokhorov; Volodymyr Kletionkin; Kateryna Martynova; Anna Nuzhna; Svitlana Klymenko; Victor Fursov; Maksym Parkhomenko (Biodiversity Data Journal)
The article represents mobilised biodata of the first part of the entomological collections of the SIZK (Schmalhausen Institute of Zoology, Kyiv) collection funds. It includes 11 occurrence datasets covering three orders and 11 families of insects: Lepidoptera (Tortricidae), Diptera (Sciaridae, Syrphidae) and Hymenoptera (Braconidae, Crabronidae, Sphecidae, Chrysididae, Ichneumonidae, Eurytomidae, Torymidae, Ormyridae). The total number of records is 12,713, based on transcription of information from the labels of pinned or slide-mounted specimens. The records cover specimens collected during 1881-2022, mostly on the territory of Ukraine, but some collections also cover the territory of other countries. The primary purpose of publishing these data is to secure the future of the SIZK collections, which are still at risk of war damage and to make the mobilised data freely and remotely accessible through GBIF.In total, three orders and 11 families of insects are represented with 12,713 records: Lepidoptera (Tortricidae), Diptera (Sciaridae, Syrphidae) and Hymenoptera (Braconidae, Crabronidae, Sphecidae, Chrysididae, Ichneumonidae, Eurytomidae, Torymidae, Ormyridae).